Enhancing Primary Education in Indonesia: Integrated Learning Policies And Artificial Intelligence Utilization - Kukuh Andri Aka; Punaji Setyosari; Endang Purwaningsih; Mardhatillah (Proceeding International Conference on Digital Education and Social Science, 2024)
Primary schools have a central role in the formation of young individuals and set an important foundation for their progress in the educational process. One of the main approaches in the elementary school context is integrated learning. This approach provides students with the opportunity to learn through themes that integrate various scientific disciplines in one learning series. Recent changes in primary school policy in Indonesia have raised concerns regarding teachers' understanding and implementation of these practices. This article outlines the concept and urgency of a deep understanding of integrated learning, which includes its four main strengths: active student involvement, holistic approach, authenticity, and meaningfulness in learning. This also explains the potential of integrated learning as a scientific background for teachers at the elementary school level. Even though education policies are constantly changing, this article emphasizes the importance of maintaining the continuity of integrated learning. Government policy support is key. This article also discusses the management of AI support as a solution to the challenges of implementing integrated learning policies in Indonesia. By utilizing AI, educators can anticipate and optimize the characteristics and advantages of integrated learning so that it is more efficient and impactful.